2020
DOI: 10.1186/s13027-020-00297-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of CTNNB1 gene mutations and expression in hepatocellular carcinoma and cirrhosis in association with hepatitis B virus infection

Abstract: Hepatitis B virus (HBV), along with Hepatitis C virus chronic infection, represents a major risk factor for hepatocellular carcinoma (HCC) development. However, molecular mechanisms involved in the development of HCC are not yet completely understood. Recent studies have indicated that mutations in CTNNB1 gene encoding for β-catenin protein lead to aberrant activation of the Wnt/ β-catenin pathway. The mutations in turn activate several downstream genes, including c-Myc, promoting the neoplastic process. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 49 publications
2
16
0
1
Order By: Relevance
“…The deregulation of different Wnt pathway genes has been repeatedly described in the recent decade (1, 31, 32), which supports the result of the current study. (38). Nevertheless, previous studies showed nuclear accumulation of β-catenin in the absence of activating mutations in hot spots of the CTNNB1 gene (39,40).…”
Section: Discussionmentioning
confidence: 94%
“…The deregulation of different Wnt pathway genes has been repeatedly described in the recent decade (1, 31, 32), which supports the result of the current study. (38). Nevertheless, previous studies showed nuclear accumulation of β-catenin in the absence of activating mutations in hot spots of the CTNNB1 gene (39,40).…”
Section: Discussionmentioning
confidence: 94%
“…In clusters 2 and 3, the patients presented with relatively low TMB, however, they carried several different genetic mutations. A previous study demonstrated that CTNNB1 mutation induced the upregulation of β-catenin expression and increased the activity of the Wnt pathway (Javanmard et al, 2020). The upregulation of c-Myc in the Wnt pathway leads to protooncogenic effects in liver malignancies (Kim et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Mutations in CTNNB1, the b-catenin encoding gene, is associated with HCC (Javanmard et al, 2020). However, genomic instability caused by HBV infection is more commonly associated with inactivating mutations in AXIN1 leading to HCC (Li et al, 2013).…”
Section: Oncogenic Viruses Subvert Wnt Signaling Through Multiple Mechanismsmentioning
confidence: 99%